HUBUNGAN CUSTOMER VALUE DENGAN KEPUTUSAN PENGAMBILAN KREDIT PADA PT. SMS FINANCE BENGKULU - Herli Widani; Rinto Noviantoro (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Herli Widani, Rinto Noviantoro; This study aims to determine the relationship between customer value and decision for withdrawal of credit in PT. SMS Finance Bengkulu. The analysis method was used Spearman Rank correlation and hypothesis test.Based on the calculation of correlation coefficient, the value of rho count (ρ) of 0.829 is in the correlation coefficient interval between 0.800-1000, the level of relationship is very strong, it means that the relationship between customer value and the decision of withdrawal of credit in PT. SMS Finance Bengkulu is very strong. Based on hypothesis test rho value calculated rho table (0.829> 0.364) so that Ho is rejected and Ha is accepted, it means that there is a significant relationship between customer value and the decision for withdrawal credit in PT. SMS Finance Bengkulu.Key Words: Customer Value, Keputusan Pengambilan Kredit.